2018
DOI: 10.1016/j.foodchem.2017.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Efficient enzyme-assisted extraction of genipin from genipap (Genipa americana L.) and its application as a crosslinker for chitosan gels

Abstract: Enzyme-assisted extraction in liquid-liquid two-phase aqueous system was applied for the first time in order to extract genipin from genipap. The effect of different commercial enzymes, their concentrations, and extraction parameters were investigated. Moreover, chitosan gels were prepared, crosslinked with glutaraldehyde or genipin and characterized by their textural and rheological properties. The crosslinked chitosan was used as support for the immobilization of model β-galactosidases. Among the different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…GEN was extracted from genipap ( Genipa americana L.) according to the method described by Bellé et al, by using the commercial enzyme Celluclast 10% (36°C, pH 3.7) in a liquid‐liquid two‐phase aqueous system consisting of distilled water and ethyl acetate. This method was reported to be simple, efficient and inexpensive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GEN was extracted from genipap ( Genipa americana L.) according to the method described by Bellé et al, by using the commercial enzyme Celluclast 10% (36°C, pH 3.7) in a liquid‐liquid two‐phase aqueous system consisting of distilled water and ethyl acetate. This method was reported to be simple, efficient and inexpensive.…”
Section: Methodsmentioning
confidence: 99%
“…According to the literature, the highest efficiency of GEN extraction from genipap was 34 mg/g, obtained by high‐pressure processing . In this sense, Bellé et al have recently used an efficient and inexpensive method based on enzyme‐assisted extraction in a two‐phase aqueous system to extract GEN from genipap fruits ( Genipa americana L.). This method resulted in the highest GEN concentration (196 mg/g) reported until now and may represent a possibility to broaden the application of GEN in the packaging field.…”
Section: Introductionmentioning
confidence: 99%
“…The previous researches confirmed that the grape skins contained a large amount of anthocyanins, and extraction of anthocyanins had become one of the alternative approaches to utilize the grape by‐products (Putnik et al., 2018). Currently, anthocyanins extraction from plant material using ultrasound‐assisted (Pinela et al., 2019), microwave‐assisted (Liu, Yang, Zhou, Wen, & Dong, 2019), enzymes‐assisted (Belle et al., 2018), and ultrahigh pressure‐assisted (Haining & Yongkun, 2017) were previously reported. Among above extraction methods, ultrasound‐assisted extraction (UAE) is a novel extraction technique, which has many merits in view of a higher yield, shorter extraction time, lower solvent consumption, temperature, and production cost in comparison to conventional solvent extraction (Pariyarath, Anal, & Sadiq, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, upon crosslinking, the pore walls become less slender and transparent. This is an evidence of the GCs framework thickening, which coheres with the confining effect Gp has towards polysaccharide and protein chains [22,23]. Since the crosslinked polymer chains possessed limited mobility, the pore formation dynamics was attuned accordingly.…”
Section: Discussionmentioning
confidence: 57%